Study of the spatial distribution of vertical and longitudinal acceleration and sensor installation position of ballast track based on wheel-rail coupling model - Ke Wang; Kun Zheng; Youjie Cai (PLoS ONE, 2025)
In order to study the basic parameters and sensitive areas of track vibration acceleration during train passage, a vehicle-rail dynamic finite element model based on wheel-rail coupled dynamics is established. The vertical and longitudinal distributions of track vibration acceleration under load are calculated with the dynamic model at the vehicle speed of 250Km/h. And the experimental modal analysis is carried out using the ballastless track mechanical test platform with pulse hammer excitation. The study found significant spatial distribution characteristics of vertical and longitudinal accelerations at different positions along the rail; the root-mean-square value is more suitable than the maximum value to represent the vibration of the whole rail span, while the entropy value can be used to analyse the vibration of the rail; wheel-rail accelerometers are very sensitive to vibration energy outside the rail head, but installing accelerometers on the outside of the rail head is difficult and may affect travel safety; it is more appropriate to choose the waist part of the rail for detection.